INTEGRASI MEDIA DIGITAL DAN PEMBELAJARAN KONTEKSTUAL UNTUK MENINGKATKAN EFEKTIVITAS PEMBELAJARAN BAHASA ARAB DAN LITERASI KEISLAMAN DI RUMAH TAHFIDZ AL-BAROKAH PALEMBANG - Sakinah Putri Wijaya; Khoirun Nida; Nabilah Aristawati; Adelia Puspita; Deany Afriany (DEVELOPMENT: Journal of Community Engagement, 2026)
This study analyzes the effectiveness of integrating information technology and contextual learning to enhance Arabic language skills among children aged 6–12 at Rumah Tahfidz Al-Barokah, Palembang. The research addresses the challenges of conventional Arabic language teaching methods that often fail to engage young learners in non-formal Islamic educational settings. Employing a descriptive qualitative approach with triangulation of sources and methods, data were collected through participatory observation, semi-structured interviews, and documentation involving eight students over two months. The study utilized pretest-posttest instruments to measure linguistic competence improvements. Results indicate a significant improvement in speaking skills (muhadatsah), with average scores increasing from 60 to 78, reading skills (qira'ah) from 65 to 80, and daily vocabulary mastery from 55 to 74. The implementation of five integrated programs—environment-based educational media, a reading corner, a waste management board, digital literacy training, and an Islamic children's festival—successfully boosted students' motivation, active participation, and linguistic competence. These findings confirm that combining digital media with contextual approaches creates a holistic learning ecosystem that addresses cognitive, affective, and psychomotor domains simultaneously. This model is recommended as a sustainable and replicable strategy for digital-era Arabic language education in similar non-formal Islamic educational institutions.